Building brand advocacy on social media to improve brand equity. (29th January 2019) - Mathur, Manisha
Social media is all about consumer networks and consumer relations that challenge marketers to leverage social media as a means to develop and improve their connections with consumers. Though tremendous opportunities via social media are alluring, businesses are still finding it hard to penetrate the clique of consumer interactions that are largely personal in nature. Despite the opportunities available through social media marketing activities, understanding customers and their behaviour, and incorporating that information in marketing strategy formulation is critical to successful strategy implementation. Thus, this study focuses attention in this direction and advances both the academic as well the practitioner literature. Theoretically grounded in two different fields-the field of sociology in combination with the field of relationship marketing, this study develops a conceptual model of driving brand advocacy and reciprocity to improve customer-based brand equity. This study uses seemingly unrelated regression technique to empirically validate our conceptual model. This paper concludes with important implications for both marketing theory and practice.